KONSTRIBUSI LOGIKA BAHASA TERHADAP RASIONALISME ISLAM - Dhairobi, Ahmad; Khudori Soleh , Ahmad (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2024)
The tradition of rational thinking in the Islamic world has actually begun since the prophetic era. This can be proven by the birth of the grammatical language initiated by Ali bin Abi Tholib and continued by Abu Aswad ad Duwali, after which a language school emerged within Islam. The aim of this study is firstly to trace the role of language logic in the development of rationalism, and secondly to answer the accusations of Western researchers (Renan and Duhem) that Islamic philosophy is plagiarised from Greek philosophy. Regarding the method and type of research, this study is a library research study with a qualitative approach where all sources are taken from the library. as for the results of this study: The current rationalism is a product of language grammars and related to the accusations of renan and duhem can be answered with 2 facts: 1. the teacher does not merely plagiarise (because Spinoza has his own philosophy even though he was previously a follower of Descartes), 2. In Islam, the concept of rationalist thinking was placed after revelation saw the weakness of reason in several ways in finding the facts of truth. 3. Rational thinking was well established before the arrival of Greek philosophy, and there were not a few rejections from Muslim scholars of Greek philosophy such as al Ghozali and other Muslim scholars. Keywords : Islamic Rationalism, Greek Rationalism, Grammar (Nahwu And Sharaf).